2020
DOI: 10.1186/s40345-020-00200-6
|View full text |Cite
|
Sign up to set email alerts
|

An evidence map of actigraphy studies exploring longitudinal associations between rest-activity rhythms and course and outcome of bipolar disorders

Abstract: Background Evidence mapping is a structured approach used to synthesize the state-of-the-art in an emerging field of research when systematic reviews or meta-analyses are deemed inappropriate. We employed this strategy to summarise knowledge regarding longitudinal ecological monitoring of rest-activity rhythms (RAR) and disease modifiers, course of illness, treatment response or outcome in bipolar disorders (BD). Structure We had two key aims: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…However, the direction of causality and specificity of these comorbidities with BD illness course are not clear. When considering actigraphy studies in exploring the course of BD over time, a systematic review of 27 studies identified rest/activity metrics including total activity, timing, and variability that were consistently associated with transition between different phases of BD that may be predictive of longitudinal course 251 …”
Section: Resultsmentioning
confidence: 99%
“…However, the direction of causality and specificity of these comorbidities with BD illness course are not clear. When considering actigraphy studies in exploring the course of BD over time, a systematic review of 27 studies identified rest/activity metrics including total activity, timing, and variability that were consistently associated with transition between different phases of BD that may be predictive of longitudinal course 251 …”
Section: Resultsmentioning
confidence: 99%
“…For instance, disruptions of CRAR have been associated with an earlier age at onset, a more unstable course of BD, suicidality, emotional dysregulation, depressive residual symptoms, worse metabolic health, poor functioning and lower response to lithium. 54,62,[80][81][82][83][84][85][86][87][88] It would be sensible to encourage more widespread longitudinal monitoring of CRAR disturbances in BD, especially as several reviews highlight that they can be effectively targeted by psychoeducational interventions (such as sleep hygiene, regular physical activity, stabilizing sleep-wake cycles) or other so called 'chronotherapeutics'. 89 In the longer term, we hope that clinical practice guidelines offer advice on the monitoring and management of CRAR in BD, as current editions do not give sufficient attention to this issue (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of CRAR in BD can enhance our research understanding of the underlying pathophysiological processes, but also it is important clinically as evidence indicates that CRAR may influence the onset, course and outcome of BD. For instance, disruptions of CRAR have been associated with an earlier age at onset, a more unstable course of BD, suicidality, emotional dysregulation, depressive residual symptoms, worse metabolic health, poor functioning and lower response to lithium 54,62,80‐88 . It would be sensible to encourage more widespread longitudinal monitoring of CRAR disturbances in BD, especially as several reviews highlight that they can be effectively targeted by psychoeducational interventions (such as sleep hygiene, regular physical activity, stabilizing sleep–wake cycles) or other so called ‘chronotherapeutics’ 89 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, wearables collecting highly detailed actigraphy, sleep and cardiovascular information have already been shown to accurately capture rest-activity rhythms, illness activity and episodes in BD [14, 10, 11]. However, their longitudinal potential on treatment response and outcomes remains poorly investigated [38]. Electrodermal activity (EDA) hyporeactivity, denoting autonomic dysfunction, has long been recognized as a strong predictive biomarker for both unipolar and bipolar depression as well as suicidal behaviour [19, 15, 36].…”
Section: Introductionmentioning
confidence: 99%